Culture Shock Pada Mahasiswa Asal Papua di Universitas Malikussaleh - Nurjannah Nasution; Safuwan Safuwan (Jurnal Psikologi Terapan, 2020)
This study aims to understand how culture shock occurs in Papuan  students in Malikussaleh University Aceh. This study was designed  with phenomenological  type by qualitative approach. Subject of this study  was selected  by purposive sampling technique, there was six students from Papua in semester one and three chosen to be subject. Data collection method used  observations and indepth interview. The  data analysis technique  used is Creswell Analysis technique by analyzing the theme and then interpreting result. The result show that  dimension  of culture shock was experienced by all of participants, Then in terms of procces culture shock, four partiscipants  has been experience and left  four phase of culture shock, and two more  are still in the third phase or recovery phase. Culture shock  has  occurs in Papuan studets  is influenced by factors such as individual difference, cross cultures experience, differences in quality, quantity  and durations of culture shock.